A corpus-based approach to Charles Dickens's use of direct thought presentation. Issue 3 (November 2018) - Ruano, Pablo
Abstract : This paper presents a corpus-based approach to Charles Dickens's use of direct thought presentation in his fifteen novels, an aspect that is traditionally under-explored, perhaps due to his characters' lack of psychological depth. Thanks to the use of corpus tools such as WordSmith Tools 7 (Scott, 2016 ) and Corpus Linguistics in Cheshire (CLiC), stretches of direct thought have been effectively retrieved and systematically scrutinised. The 244 stretches of direct thought presentation identified here have revealed meaningful patterns in form and function so far as Dickens's use of this mode of presentation is concerned. Not only will the analysis of these patterns give us a better understanding of Dickens's style, but it will also reinforce the findings discussed in Busse's (2010) study of direct thought presentation in nineteenth-century English fiction – the most comprehensive analysis to date.